2011
DOI: 10.1016/j.bbr.2010.08.039
|View full text |Cite
|
Sign up to set email alerts
|

General and social anxiety in the BTBR T+ tf/J mouse strain

Abstract: BTBR T+ tf/J (BTBR) is an inbred mouse strain that shows behavioral traits with analogies to the three diagnostic symptoms of autism spectrum disorder (ASD); deficits in social interaction, impaired communication, and repetitive behaviors with restricted interests. Previous findings reveal that when compared to C57BL/6J (B6) and other inbred strains, BTBR exhibit normal to low anxiety-like traits in paradigms designed to assess anxiety-related behaviors. The current study assessed the generality of these anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
75
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 61 publications
13
75
2
Order By: Relevance
“…4e). These findings strongly support previous studies that suggested a social behaviour deficiency in the BTBR mouse strain 29,31 . Moreover, we found that by using four social behaviour features collected by the system in a single testing day, we could predict the mouse strain with an accuracy of about 90-95% (see Methods and Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4e). These findings strongly support previous studies that suggested a social behaviour deficiency in the BTBR mouse strain 29,31 . Moreover, we found that by using four social behaviour features collected by the system in a single testing day, we could predict the mouse strain with an accuracy of about 90-95% (see Methods and Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
“…The integrated video-RFID system was applied to test two inbred mouse strains: C57BL/6 Â 129Sv (C57 Â 129) and BTBR T ĂŸ tf/J (BTBR), which were previously reported to exhibit significantly different behavioural phenotypes [29][30][31] . Three independent groups of mice were tested for each of the mouse strains (that is, a total of six experiments), using an identical standard operation protocol; the duration of each experiment was 8 days.…”
Section: Resultsmentioning
confidence: 99%
“…Further, these types of mice have been analyzed using various behavioral tests including an elevated plus maze, a mouse defense battery, an elevated zero-maze, a three-chambered social approach test, etc. (Bolivar et al, 2007;Meyza et al, 2013;Moy et al, 2007;Pobbe et al, 2011;Silverman et al, 2010;Wohr et al, 2011). Since numerous immune abnormalities have been reported in autism (Ashwood & van de Water, 2004;Stigler et al, 2009), the current study investigated the immune system of BTBR mice.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the BTBR mice still inchworm, but at a lower frequency and duration, thus indicating that the inchworming behavior is a stereotypic behavior possibly induced by social anxiety (data not shown). However, given that studies have failed to reliably demonstrate differences in anxiety between the BTBR and B6 control mice, anxiety is likely a interacting with other factors to induce this behavior 12 . However, the focus of this methodological article was the standardized modification to the juvenile social interaction protocol because it elicits the behavior rapidly and reliably, with dramatic differences between BTBR and B6 mice.…”
Section: Discussionmentioning
confidence: 99%